Critical illness and multi‐organ failure following topical application of skin‐lightening preparation. Issue 1 (11th June 2019) - Rudge, J. E.; Raithatha, M.
Summary: Topical application of skin‐lightening cream is increasingly undertaken in many non‐Caucasian populations for cultural and social reasons. It is a rare cause of poisoning that has potential to lead to significant harm due to skin damage and systemic absorption of cream following application over prolonged periods of time. This case report describes for the development of multi‐organ failure in an adult due to salicylate toxicity after whole‐body application of a skin‐lightening cream for 24 h. It highlights the need for vigilance and awareness of the toxic potential of topical salicylates.